An American son : a memoir - Rubio, Marco, 1971- (New York : Sentinel, 2012)
Rubio, U.S. senator and son of Cuban immigrants, tells his "American dream" story as he speaks on the national stage about the challenges we face and the better future that's possible if we return to our founding principles
Keywords: Rubio, Marco, -- 1971-; United States. -- Congress. -- Senate -- Biography; Legislators -- United States -- Biography; Legislators -- Florida -- Biography; Cuban Americans -- Florida -- Biography; United States -- Politics and government -- 2009-; Florida -- Politics and government -- 1951-; Florida -- Biography